THE EFFECT OF COMBINATION OF ANTACID AND CIPROFLOXACIN ON BIOAVAILAIBILITY OF CIPROFLOXACIN: the effect of the antacid administration time interval on the pharmacokinetic parameter values ​​of ciprofloxacin - idr, Parhan; Suwarso, Edy (Asian Journal of Pharmaceutical Research and Development, 2019)
Most people use drugs at the same time. This concomitant use is susceptible to interaction which results in reduced bioavailability of one of the drugs. Ciprofloxacin is often used to prevent gram-positive and negative bacterial infections. One of them is for gastrointestinal infections. This causes most of the use of ciprofloxacin often combined with antacids. Fluoroquinolone antibiotics, one of which is ciprofloxacin when given together with antacids, can cause chelate compound formation. This causes a reduced bioavailability of ciprofloxacin in the body. The purpose of this study was to see the differences in the bioavailability of single ciproloxacin with the bioavailability of ciprofloxacin in combination with antacids. Analysis of ciprofloxacin levels in the blood was analyzed using a High Performance Liquid Chromatography (HPLC) apparatus. The results showed a significant difference between the bioavailability parameters of a single ciprofloxacin against the bioavailability of a combination antacid Ciprofloxacin. ciprofloxacin in combination with antacids has different bioavailability with single ciprofloxacin